Integration of Traditional Medicine in the Perspective of Islamic Law and Positive Law - Dilla, Nur Indah Rahma; Irwansyah, Irwansyah; Atifah, Nur (PROMOTOR, 2024)
Traditional medicine in Indonesia, as part of the archipelago's cultural heritage, has been the main choice in curing people's illnesses. Despite the growth of modern medical services, many still rely on traditional medicine, including reflexology, herbal drinks, aromatherapy, chiropractic therapy, cupping, and acupuncture. This study aims to examine and discuss traditional medicine in Indonesia, focusing on Battra (traditional medicine) and various types of traditional medicine such as reflexology, herbal drinks, aromatherapy, chiropractic therapy, cupping, acupuncture, as well as traditional medicine in the context of Islamic law. This research uses a descriptive qualitative approach through literature study. The results show that there is a link between the social relationship between traditional healers and patients as a legal relationship in terms of their respective interests. In addition, traditional medicine in Indonesia is not only seen as a cheap alternative, but also as an inseparable part of cultural identity and ancestral heritage that needs to be preserved. Health law also plays a role in regulating and protecting traditional medicine to prevent abuse and harmful practices.